2015
DOI: 10.1007/s00228-015-1891-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the heterogeneity of studies estimating the association between risk factors and the use of potentially inappropriate drug therapy for the elderly: a systematic review with meta-analysis

Abstract: Twenty-nine articles (17 cross-sectional and 12 cohort) were included. The majority of the studies were conducted in Europe. Regarding the study durations, 3 to 18 months was necessary to perform the research. As for the sample characteristics, all the studies analyzed involved the older adults and included anywhere from 96 patients to 33,830,599 outpatient consultations. Of the variables analyzed, only polypharmacy presented a positive association with the use of PIDT. All meta-analysis studies showed high he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 67 publications
(51 reference statements)
2
18
2
2
Order By: Relevance
“…Second, as we used only the prescription record of the EMR, we did not have information on the general health status and co-morbidities of the patients. Thus, although PIMs have been associated with many chronic diseases,161820) we were unable to analyze associations with any disease in our study. Third, despite the widespread use of the Beers criteria for evaluating PIMs, there is considerable debate concerning the efficacy of the criteria.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Second, as we used only the prescription record of the EMR, we did not have information on the general health status and co-morbidities of the patients. Thus, although PIMs have been associated with many chronic diseases,161820) we were unable to analyze associations with any disease in our study. Third, despite the widespread use of the Beers criteria for evaluating PIMs, there is considerable debate concerning the efficacy of the criteria.…”
Section: Discussionmentioning
confidence: 84%
“…Many studies have reported an increased risk of PIM with age, sex, multiple medications, and the number of co-morbidities 1011121415161819). In Brazil, PIM use in older patients increased with increasing age and female sex 19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a medication that is known to induce harmful effects through drug-drug or drug-disease interactions are also inappropriate, as well as the prescription of a high-dose medication during an excessive period of time (Lang et al 2010). Potentially inappropriate psychotropic (PIP) prescription in the elderly patients (≥65 years) has become an important concern in developed countries (Nishtala et al 2014;Santos et al 2015a). With the global increase of medication prescription, the increase of life expectancy and the improvement of screening strategies, the global medication rate has increased in the elderly (Santos et al 2015b).…”
Section: Introductionmentioning
confidence: 99%